Low‐Temperature Magnetic and Dielectric Anomalies in Rare‐Earth‐Substituted BiFeO3 Ceramics. Issue 12 (6th November 2014) - Koval, Vladimir; Skorvanek, Ivan; Yan, Haixue
Abstract : In this work, we report on the magnetic and dielectric anomalies observed in dense Bi1– x RE x FeO3 ceramics (RE = Dy, Tb; 0 ≤ x ≤ 0.3) at cryogenic temperatures. For compositions with a high content of rare‐earth ions, thermomagnetic experiments revealed a distinct anomaly in the magnetization curves at temperatures below 200 K. The temperature of the magnetic anomaly along with a thermal hysteresis was found to be dependent on the rare‐earth concentration and magnetic field strength. Low‐temperature dielectric measurements showed an anomalous relaxor‐like behavior of the relative permittivity and dielectric loss in highly doped ceramic samples. The anomalies in low‐temperature magnetization and dielectric response are suggested to result from the presence of GdFeO3 ‐like orthoferrite phase and/or bismuth rare‐earth‐mixed iron garnet impurities.